Huang-Lian-Jie-Du Decoction Attenuates Atherosclerosis and Increases Plaque Stability in High-Fat Diet-Induced ApoE-/- Mice by Inhibiting M1 Macrophage Polarization and Promoting M2 Macrophage Polarization - Cai, Yinhe; Wen, Junmao; Ma, Siwen; Mai, Zhexing; Zhan, Qunzhang; Wang, Yijun; Zhang, Yueyao; Chen, He; Li, Haiyi; Wu, Wei; Li, Rong; Luo, Chuanjin (Frontiers in Physiology, 2021)
Macrophage polarization plays a vital impact in triggering atherosclerosis progression and regression. Huang-Lian-Jie-Du Decoction (HLJDD), a famous traditional Chinese decoction, displays notable anti-inflammatory and lipid-lowering effects in different animal models. However, its effects and mechanisms on atherosclerosis have not been clearly defined. We determined whether HLJDD attenuated atherosclerosis and plaques vulnerability by regulating macrophage polarization in ApoE-/- mice induced by high-fat diet. Furthermore, we investigated the effects of HLJDD on macrophage polarization in oxidized low-density lipoprotein (ox-LDL) induced RAW264.7 cells. For in vivo assay, compared with the model group, HLJDD ameliorated lipid metabolism, with significantly decreased levels of serum triglyceride, total cholesterol and lipid density lipoprotein. HLJDD suppressed serum TNF-α and IL-1β levels with increased serum IL-10 level, and inhibited mRNA level of NLRP3 inflammasome in carotid tissues. HLJDD enhanced carotid lesion stability by decreasing macrophage infiltration together with increased expression of collagen fibers and α-SMA. Moreover, HLJDD inhibited M1 macrophage polarization, which decreased the expression and mRNA levels of M1 markers (iNOS and CD86). HLJDD enhanced alternatively activated macrophage (M2) activation, which increased the expression and mRNA levels of M2 markers (Arg-1 and CD163). For in vitro assay, HLJDD inhibited foam cell formation in RAW264.7 macrophages disturbed by ox-LDL. Besides, groups with ox-LDL plus HLJDD drug had a lower expression of CD86 and mRNA levels of iNOS, CD86 and IL-1β, but higher expression of CD163 and mRNA levels of Arg-1, CD163 and IL-10 than ox-LDL group. Collectively, our results revealed that HLJDD alleviated atherosclerosis and promoted plaque stability by suppressing M1 polarization and enhancing M2 polarization.